Neural correlates of prediction violations in boys with Tourette syndrome: Evidence from harmonic expectancy. (17th February 2018) - Buse, Judith; Beste, Christian; Roessner, Veit
Abstract: Objectives: It has been suggested that Tourette syndrome (TS) might be associated with alterations of the attention system, but the nature of these alterations and the underlying neuroanatomical network remains elusive. We aimed at investigating the functional neuroanatomical modulators of attention allocation towards predictable versus unpredictable stimuli in boys with TS. Methods: Using functional magnetic resonance imaging, we ran a harmonic expectancy violation paradigm in 17 boys with TS and 23 matched healthy controls (HCs). We presented chord sequence in which the first four chords induced a strong expectancy for a harmonic chord at the next position. In 70% this expectancy was fulfilled (harmonic), in 30% the expectancy was violated (disharmonic). Results: HCs responded faster to the disharmonic compared to harmonic chords, indicating a stronger attention allocation towards unpredictable stimuli, while this effect was not found in boys with TS. HCs showed stronger anterior cingulate cortex (ACC) activation during disharmonic compared to harmonic chords. Boys with TS showed stronger ACC activation during harmonic chords, which was associated with greater tic severity. Conclusions: Our findings indicate that boys with TS showed altered reactions towards predictable versus unpredictable stimuli in brain regions playing an important role in attention control. This might indicate altered allocation of attention towards those stimuli.